HUBUNGAN UMUR DAN LAMA PENGGUNAAN IUD DENGAN EFEK SAMPING PENGGUNAAN IUD - Widyaningtyas, Radicha Nur; Wahyuningsih, Heni Puji; Estiwidani, Dwiana (Poltekkes Kemenkes Yogyakarta, 2015)
Acceptors IUD inlridonesia tending to decline. Based on data SDKI 2012 recorded 3.9 % PUS use contraceptives IUD. Oneconsideration IUD election is the existence of a side effect. Mejing Wetan having acceptors IUD the largest one in theAmbarketawang Villages a number of 52 people. The purpose of this research is to knew age and the long used of with the sideeffects of the used IUD at Mejing Wetan 2015. The research is survey analytic by approach cross sectional and use saturatedsampling. An instrument of a chief. The subject of study are 52 acceptors IUD. Data analysis using analysis univariatand bivariat andstatistict test of chi square with ? 0,05. From this research was obtained the result of p value 0,026 which there are between agesrelation with one side effect in the formof pain with contingency coefisient 0,35 and the result ofp value 0.028whichmeans there arerelationship beween long the use of to one side effect of the change menstrual with contingency coefisient 0,347. Conclussionresearch is there is meaningful in statistc between the ages of with side effects iud of pain and there are the relationship between longthe use of to change in themenstrual.